The significance of nutrition on patients initiated on antiretroviral therapy at Gelukspan District Hospital - Kachabe, Serguis Jim (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.